Conditionals and Compositionality - Higginbotham, James (Noûs (Bloomington, Indiana), 2003)
Indicative conditionals of the type Everyone will succeed if he works hard/no one will succeed if he goofs off, held by Higginbotham (1986) to be a counterexample to compositionality as the interpretation of the if-clause depends on external information, are examined in the framework of Robert Stalnaker's (1968) analysis, especially his principle of conditional excluded middle. Although the counterthesis that takes the conditional clause as the restriction on the quantifier apparently resolves the example case above, it is shown not to hold in general, as absorption of the conditional into the quantified antecedent subject alters the interpretation in a wide range of sentences. Compositionality is partially restored, however, under a proposed generalization of counterfactual irrelevance, which may belong to the pragmatics of conditionals: if the antecedent is counterfactually irrelevant to the consequent, the Stalnaker indicative conditional is equivalent to the corresponding material conditional. In this framework, quantified conditionals receive the same analysis whether their quantifiers are monotone increasing or monotone decreasing; the conditional excluded middle is presupposed in general by quantified conditionals whose quantifiers are not monotone increasing. 6 References. J. Hitchcock